2011
DOI: 10.1016/j.jmii.2011.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Microbial isolation and emergence of antimicrobial resistance associated with tigecycline usage

Abstract: The most common pathogens isolated in patients receiving tigecycline were A baumannii and P aeruginosa. Tigecycline usage decreased the isolation frequency of A baumannii, methicillin-resistant S aureus, E coli, and K pneumoniae. Exposure to tigecycline may be associated with a decreased susceptibility rate of A baumannii for tigecycline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Carbapenem-resistant E. cloacae subpopulations were characterized by (1) downregulation of ompF gene, which encodes protein with extensive transmembrane channels, and (2) the polarization of OM transcriptome-balance, which was sloped toward ompC gene, encoding proteins recently reported to possess restrictive transmembrane channels. The growing prevalence of pathogens resistant to most or even all currently available antimicrobial agents heralds the potential risk of a future “post-antibiotic era” (Falagas and Bliziotis, 2007; Livermore, 2009; Hornsey et al, 2010; Chen et al, 2011; Bergen et al, 2012; Diena et al, 2012; Majewski et al, 2012, 2014b; Yahav et al, 2012; Linkevicius et al, 2013; Veleba et al, 2013; Deng et al, 2014). Great effort needs to be taken to explore the background of resistance to antimicrobials of “last-resort.”…”
Section: Discussionmentioning
confidence: 99%
“…Carbapenem-resistant E. cloacae subpopulations were characterized by (1) downregulation of ompF gene, which encodes protein with extensive transmembrane channels, and (2) the polarization of OM transcriptome-balance, which was sloped toward ompC gene, encoding proteins recently reported to possess restrictive transmembrane channels. The growing prevalence of pathogens resistant to most or even all currently available antimicrobial agents heralds the potential risk of a future “post-antibiotic era” (Falagas and Bliziotis, 2007; Livermore, 2009; Hornsey et al, 2010; Chen et al, 2011; Bergen et al, 2012; Diena et al, 2012; Majewski et al, 2012, 2014b; Yahav et al, 2012; Linkevicius et al, 2013; Veleba et al, 2013; Deng et al, 2014). Great effort needs to be taken to explore the background of resistance to antimicrobials of “last-resort.”…”
Section: Discussionmentioning
confidence: 99%
“…40 The other notable finding is that B. cepacia emerged as the main organism of breakthrough bacteremic episodes after tigecycline-imipenem/cilastatin salvage therapy against the VAP due to XDR-Ab isolates, in distinction from that described for the patients receiving tigecycline treatment. 41 It is not surprising since B. cepacia are mostly in vitro non-susceptible to tigecycline and imipenem/cilastatin. 5 The checkerboard MIC analysis, a method of controversial reproducibility, was considered to under-estimate the synergistic potential against non-fermentative GNB as compared with the time-kill study.…”
Section: Data Of the In Vitro Synergy Tests And Pcr Studymentioning
confidence: 99%
“…One study showed a superinfection rate of 23.5% during tigecycline treatment and that Pseudomonas aeruginosa was the most frequently found organism, responsible for 58.3% of superinfections. Other studies found that Acinetobacter baumannii and P. aeruginosa were the two most common superinfection organisms during tigecycline treatment (9,13,14). To our knowledge, this is the first study to identify risk factors for acquisition of Pseudomonas or Proteus spp.…”
mentioning
confidence: 75%
“…However, the U.S. Food and Drug Administration noted that, in a pooled analysis of 13 clinical trials, tigecycline was significantly associated with an increased risk for all-cause mortality compared to that of other antibiotics used to treat serious infections and announced that it has added a boxed warning about the increased risk for death to the label of tigecycline (7). Nevertheless, the unique spectrum of activity and favorable postantibiotic effect make tigecycline an important antibiotic in clinical practice (1)(2)(3)(8)(9)(10), particularly for complicated skin and soft tissue infections and the complicated intra-abdominal infections for which it is indicated (1,3,8,10). However, as tigecycline has no activity against Pseudomonas and Proteus species, there are concerns about the possibility of superinfection caused by these organisms (11,12).…”
mentioning
confidence: 99%